THE IMPACT OF THE COVID-19 PANDEMIC ON LABOR RELATIONS IN THE INDONESIAN OIL AND GAS INDUSTRY FROM THE PERSPECTIVE OF LABOR LAW - Arifin Mursan, Usman; Sinurat, Sahat (Sean Institute, 2022)
This study aims to find out whether the Covid-19 pandemic can be used as one of the reasons for the efficiency of companies in Oil and Gas (MIGAS) Industry to carry out Termination of Employment (PHK). The type of method used in writing this description is a normative legal research method using secondary data sources, namely through the statutory approach, conceptual approach and case approach. The data collection technique in writing this paper uses library research and the data is then analyzed qualitatively. The results of this study conclude that the Covid-19 pandemic cannot be directly used as the basis for the inability of parties in the Oil and Gas (MIGAS) industry to fulfill their achievements. It is necessary to prove a causal relationship that it is true that the inability is caused directly by the influence of the Covid-19 pandemic but is more emphasized on renegotiation of work agreements affected by the Covid-19 pandemic ending in deliberation and consensus in this case if Termination of Employment (PHK) is done, the employer continues to pay compensation to the Worker.